Investigation of the differences between the Tibetan and Han populations in the hemoglobin–oxygen affinity of red blood cells and in the adaptation to high-altitude environments. Issue 5 (28th May 2018) - Li, Cuiying; Li, Xiaowei; Liu, Juan; Fan, Xiu; You, Guoxing; Zhao, Lian; Zhou, Hong; Li, Jingqi; Lei, Huifen
ABSTRACT: Objective: High altitude is characterized by low oxygen pressure, resulting in multiple adaptive responses. Tibetans who have lived in the plateau for thousands of years have developed unique phenotypes, such as downregulation of the HIF pathway through EPAS1 and EGLN1 gene mutation. However, the changes of hemoglobin–oxygen affinity under hypoxia environment remain elusive. Methods: A blood cell analyzer and a blood oxygen analyzer were used to conduct routine blood tests and measure the oxygen affinity P 50 in in the Han population that rapidly entered the plateau (for 3–7 days), the plateau-acclimatized Han population (residing for 30 days on the plateau), the plateau Han population (more than 10 years on the plateau), and the Tibetan population. Results: The Han population that rapidly entered the plateau had increasing higher P 50 values, RBCs counts and hemoglobin (HGB) levels, while the acclimatized Han population, the plateau Han population and Tibetan all had significantly lower P 50 values. However, there were no significant differences in the RBCs counts and HGB levels between the plateau Han, Tibetan populations and the Han population of the plains. Discussion: The adaptability of the Tibetan and plateau Han populations to the plateau was mainly due to the strong affinity of HGB for oxygen, which provided sufficient oxygen for tissues and organs. Conclusions: The change of P 50 could be a feature of the adaptation to the plateau and to avoid altitude sickness, such as high-altitude polycythemia and dyspnea.